State of the art of prostatic arterial embolization for benign prostatic hyperplasia - Petrillo, Mario (Gland Surg, 2018)
Prostatectomy via open surgery or transurethral resection of the prostate (TURP) is the standard treatment for benign prostatic hyperplasia (BPH). Several patients present contraindication for standard approach, individuals older than 60 years with urinary tract infection, strictures, post-operative pain, incontinence or urinary retention, sexual dysfunction, and blood loss are not good candidates for surgery. Prostatic artery embolization (PAE) is emerging as a viable method for patients unsuitable for surgery. In this article, we report results about technical and clinical success and safety of the procedure to define the current status.